A comparative cost analysis of 25-fraction vs 5-fraction postoperative radiotherapy regimens for breast cancer - Dem Aliaj; Guido Schüpfer; Gabriela Studer (Swiss Medical Weekly)
PURPOSE: To compare the costs of 25-fraction vs 5-fraction postoperative radiotherapy regimens in breast cancer patients. Several clinical trials have confirmed at least comparable safety and efficacy of short hypofractionated partial and whole breast radiation regimens. This study was focused on providing detailed cost data and analysing the advantages or disadvantages of either treatment strategy for patients.